Crusted Demodicosis in an Immunocompetent Pediatric Patient - Guillermo Antonio Guerrero-González; Maira Elizabeth Herz-Ruelas; Minerva Gómez-Flores; Jorge Ocampo-Candiani (Hindawi Limited, 2014)
Demodicosis refers to the infestation by Demodex spp., a saprophytic mite of the pilosebaceous unit. Demodex proliferation can result in a number of cutaneous disorders including pustular folliculitis, pityriasis folliculorum, papulopustular, and granulomatous rosacea, among others. We report the case of a 7-year-old female presenting with pruritic grayish crusted lesions over her nose and cheeks, along with facial erythema, papules, and pustules. The father referred chronic use of topical steroids. A potassium hydroxide mount of a pustule scraping revealed several D. folliculorum mites. Oral ivermectin (200 μg/kg, single dose) plus topical permethrin 5% lotion applied for 3 consecutive nights were administered. Oral ivermectin was repeated every week and oral erythromycin plus topical metronidazole cream was added. The facial lesions greatly improved within the following 3 months. While infestation of the pilosebaceous unit by Demodex folliculorum mites is common, only few individuals present symptoms. Demodicosis can present as pruritic papules, pustules, plaques, and granulomatous facial lesions. To our knowledge, this is the first reported case of facial crusted demodicosis in an immunocompetent child. The development of symptoms in this patient could be secondary to local immunosuppression caused by the chronic use of topical steroids.